Team Leadership and Team Cultural Diversity: The Moderating Effects of Leader Cultural Background and Leader Team Tenure. (August 2021) - Raithel, Katja; van Knippenberg, Daan; Stam, Daan
By bringing team members with different cultural backgrounds together, teams in international business can benefit from cultural diversity and reach higher levels of performance. Cultural diversity also brings challenges, however, and diversity research has identified the need to consider moderating influences in the diversity–performance relationship. Team leadership should be particularly important in this respect and drawing on a theoretical analysis that puts an understanding of cultural diversity center stage, we propose that factors that reflect leaders' experience with cultural diversity positively moderate the relationship between cultural diversity and team performance. We identify leader cultural background (local vs. foreign to the host culture) and leader team tenure as such factors. We predict that the influence of team nationality diversity (a form of cultural diversity) on team performance is more positive with a leader who is foreign to the host country than with a local leader, and with a leader with longer team tenure. In addition, we predict that the one moderating influence substitutes for the other, such that the effect of leader cultural background is stronger for leaders with shorter tenure with the team. Results from a survey of N  = 66 teams ( N  = 336 individuals) from a multinational company support these hypotheses and inform our discussion of ways forward in the study of leadership and team diversity.